A new compact young moving group around V1062 Scorpii - Röser, Siegfried; Schilbach, Elena; Henning, Thomas (Astronomy and astrophysics, 2018)
Aims. We are searching for new open clusters or moving groups in the solar neighbourhood.Methods. We used the Gaia-TGAS catalogue, cut it into narrow proper motion and parallax slices and searched for significant spatial over-densities of stars in each slice. We then examined stars forming over-densities in optical and near-infrared colour-magnitude diagrams to determine if they are compatible with isochrones of a cluster.Results. We detected a hitherto unknown moving group or cluster in the Upper Centaurus Lupus (UCL) section of the Scorpius-Centaurus OB association (Sco-Cen) at a distance of 175 pc from the Sun. It is a group of 63 comoving stars of less than 10 to about 25 Myr in age. For the brightest stars that are present in the Gaia-TGAS catalogue, the mean difference between kinematic and trigonometric distance moduli is − 0.01 mag with a standard deviation of 0.11 mag. Fainter cluster candidates are found in the HSOY catalogue, where no trigonometric parallaxes are available. For a subset of our candidate stars, we obtained radial velocity measurements at the MPG/ESO 2.2 m telescope in La Silla. Altogether we found 12 members with confirmed radial velocities and parallaxes, 31 with parallaxes or radial velocities, and 20 candidates from the convergent point method. The isochrone masses of our 63 members range from 2.6 to 0.7 M⊙.